Fluorescence enhancement of immunoarrays by gold and silica nanoparticles - Ramoo, Jeevaneswaran (2010)
High-throughput protein microarrays have advanced scientific study into previously very complicated fields such as identification of diseases related proteins and their respective functions. However, they are still not as successful as DNA microarrays in terms of practical usage in medical field. One of the many reasons is due to low detection signal from microarrays. Hence, they are incapable of producing high quality data from small samples of proteins which is frequent in clinical environment. Hence, this project aim is to improve the fluorescence signal from immunoarrays, a subset of protein microarrays. Two different mechanisms, Surface Plasmon Resonance and Enlarged Receptor Surface, were explored to improve fluorescence signal of immunoarrays. For these mechanisms, gold nanoparticles and silica nanoparticles were needed and they were synthesized by Turkevich method and Stober method respectively. Both mechanisms successfully enhanced fluorescence signals. Surface Enlarged receptor method with silica nanoparticles immobilized on microarray substrate enhanced fluorescence signal 7.3 times. On the other hand, silica coated gold nanoparticles enhanced fluorescence signal by 2.75 times in solution. By no means, these are the best possible enhancements as parameters affecting both mechanisms can be optimized further to produce higher fluorescence signal which will enable detection of protein samples of low concentration.